Role of insulin in lipoprotein secretion by cultured rat hepatocytes. - Patsch, W (1983)
To study the effect of insulin on lipoprotein synthesis and secretion by the liver, apoprotein and lipid levels were measured in primary rat liver cell cultures grown on fibronectin-coated dishes. Triglycerides, phospholipids, apoprotein (apo) B, apo-E, and apo-C-III3 all accumulated in culture media linearly for periods up to 20 h. During incubations, cellular triglyceride contents increased slightly, while cellular apoprotein and phospholipid contents remained constant. In the absence of insulin, rates of accumulation in media of triglycerides, apo-B, apo-C-III3, and apo-E were 2.5 +/- 0.3 micrograms/mg and 33 +/- 5, 24 +/- 3, and 162 +/- 32 ng/mg cell protein per h, respectively. On gel permeation chromatography and density gradient ultracentrifugation, the majority of apoproteins in media were found to be associated with very low density lipoproteins (VLDL) and very little eluted or sedimented with albumin. Incubations in the presence of 50-800 microU/ml of insulin resulted in dose-dependent decreases of triglyceride, phospholipid, apo-B, and apo-E accumulation in the media, paralleled by increases in the cellular contents of these lipoprotein components. The inhibitory effects of insulin on secretion were reversible. Levels of apo-C-III3 and albumin were not affected by insulin. In addition to decreasing secretory rates, the proportion of apo-B, apo-E, and apo-C-III3 associated with VLDL also decreased after the addition of insulin. Concomitantly, the proportion of apo-B eluting with LDL and apo-C-III3, and apo-E eluting near albumin increased. Control experiments, in which exogenous 125I-VLDL or endogenously labeled [14C]VLDL were added to cultures, revealed that the insulin-induced differences in VLDL accumulation and the lipid association of media apoproteins were not due to differences in the processing of VLDL by cells cultured in the presence or absence of insulin. Therefore, it appears that insulin may inhibit the secretion of VLDL perhaps by reducing the intracellular association of lipids and apoproteins.